Effect of staining agents on color change of composites - Mateus Rodrigues Tonetto; Carolina Santezi Neto; Cristina Magnani Felício; Patrícia Aleixo dos Santos Domingos; Edson Alves de Campos; Marcelo Ferrarezi de Andrade (Revista Sul-Brasileira de Odontologia, 2013)
Composite resins are materials that can present color changing when exposed to pigments. Objective: The aim of this study was to evaluate, in vitro, the color changing of composites after immersion in different substances for different periods. Material and methods: Two microhybrid composite resins: Charisma (Heraeus – Kulzer) and Opallis (FGM) were used. Red wine and acai pulp were also used as immersion medium. For this study, 32 specimens with 10 mm of diameter and 2 mm of thickness were used, divided into 4 groups: Group 1 – Opallis composite immersed in red wine solution; Group 2 – Opallis composite immersed in acai berry pulp solution; Group 3 – Charisma composite immersed in red wine solution; Group 4 – Charisma composite immersed in acai berry pulp solution. The specimens were evaluated in the following time periods: T0 – baseline, T1 – 24 hours, T2 – 48 hours, T3 – 72 hours and T4 – 96 hours. For the assessment of staining, a spectrophotometer for colorimetry was used (Color Guide 45 / 0, PCB 6807 BYK-Gardner Gerestsried GmBH, Germany), and the values obtained were transferred to a computer and recorded according to CIELAB system. Results: The data were evaluated using Kruskal-Wallis non-parametric tests with the following ΔE mean values for the immersion periods of 24, 48, 72 and 96 hours, respectively: G1 – 7.35, 7.84, 9.04,10.48; G2 – 2.92, 4.15, 4.30, 4.64; G3 – 3.14, 7.35, 8.13, 8.43, G4 – 4.49, 5.99, 6.92, 6.76. Conclusion: Red wine showed a higher tendency toward altering the composite color than acai berry pulp. In addition, no significant difference was found concerning to the behavior of the two composite resins. Concerning to the immersion time periods, significant differences were only observed among the groups in the 24 hour time period.